UNDERSTANDING THE PURCHASING PORTFOLIO MODEL – A JUST-IN-SEQUENCE APPROACH INCREASING MANUFACTURING EFFICIENCY - Juhász, János; Dr. Bányai, Tamás (Journal of Applied Engineering Science, 2021)
Just-in-sequence supply solutions are highly searched problems of the scheduling the manufacturing and logistics resources. The cost reduction, efficiency and capacity utilization are based on the controlled and designed parameters of the participants' supply processes and services. To increase logistic operations and other services in supply chain’s inventory activities, the optimization of the supply process is unavoidable. The aim of this article to measure the efficiency of the supply chain’s inventory activities in manufacturing technology processes. Based on the results of the application of our ABC-XYZ model approach to defines the importance of product values in the inventory management systems. The case study and computational results validate the matrix model and evaluates its efforts to renewing manufacturing and delivery processes's efficiency in inventory strartegies based on just-in-sequence strategy.
Keywords: logistics; manufacturing technology; purchasing; procurement